Living with Tinnitus: A Qualitative Exploration of Indonesian Patients' Coping Strategies and Support Needs - Venny Meilinda; Michelle Birne; Mariana Alifah; Imanuel Simbolon (Phlox Institute: Indonesian Medical Research Organization, 2023)
Introduction: Tinnitus, the perception of sound without an external source, affects many people globally. Its causes are varied and often unclear, and it can significantly impact the quality of life, causing distress, sleep problems, and concentration difficulties. This study explored the experiences of Indonesian tinnitus patients, focusing on their coping strategies and support needs. Methods: We conducted semi-structured interviews with 25 Indonesian adults diagnosed with tinnitus. Participants were recruited from otorhinolaryngology clinics in Jakarta and Surabaya. Interviews were audio-recorded, transcribed, and analyzed using thematic analysis. Results: Four main themes emerged: (1) The multifaceted impact of tinnitus: emotional distress, social isolation, and functional limitations; (2) Diverse coping mechanisms: acceptance, sound therapy, and traditional remedies; (3) Perceived support needs: desire for information, counseling, and support groups; and (4) Cultural influences: spiritual beliefs and alternative medicine. Conclusion: This study provides valuable insights into the experiences of Indonesian tinnitus patients. It highlights the need for culturally sensitive and holistic management, including comprehensive support services like information, counseling, and support groups tailored to their needs.